Criteria,institusional,and priority policies in mitigating conflict between human and Tapanuli orangutans in North Sumatra - Wanda Kuswanda (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2022)
The conflict between humans and orangutan tapanuli (Pongo tapanuliensis) in North Sumatra has increased in the last five years. Their conflicts are caused by deforestation, land clearing, crop damage, and climate change. This study aims to obtain information on criteria and priority institutions as well as policy recommendations in mitigating human-orangutan tapanuli conflict to create a harmonious relationship between them in the future. We have collected data by distributing questionnaires by the Analytical Hierarchy Process (AHP) method and structured interviews. Data analysis was carried out using Expert Choice and Microsoft Excel 2010 Software. The priority criteria were ecological restoration (habitat and population) and community economic empowerment. The most appropriate institutions to implement the mitigation program are the government and customary institutions. Private companies and NGOs can support and engage in government programs. The recommended policies and programs include 1) the parties to encourage regulations for dealing with human-wildlife conflicts (Permenhut No. 48 of 2008) into government regulations; 2) restoration of the ecological needs of orangutans through increasing security in conservation forests, establishing animal conservation blocks in the Forest Management Unit and developing animal corridors; and 3) increasing economic empowerment and local wisdom of the community through the development of ecotourism villages, building fishery and animal husbandry centers and increasing the role of local wisdom in land management. Keywords: conflict, government, community, tapanuli orangutans; forest.